"You are not a man": a multi‐method study of trans stigma and risk of HIV and sexually transmitted infections among trans men in Uganda. Issue 12 (29th December 2021) - Mujugira, Andrew; Kasiita, Vicent; Bagaya, Monica; Nakyanzi, Agnes; Bambia, Felix; Nampewo, Oliva; Kamusiime, Brenda; Mugisha, Jackson; Nalumansi, Alisaati; Twesigye, Collin C.; Muwonge, Timothy R.; Baeten, Jared M.; et al.
Abstract: Introduction: Transgender (trans) men in sub‐Saharan Africa are a hidden and vulnerable population who may engage in sex work due to socio‐economic exclusion and lack of alternative employment opportunities. Little is known about HIV and sexually transmitted infection (STI) risk among trans men in this setting. We conducted a multi‐method study to characterize HIV/STI risk among trans men in Uganda. Methods: Between January and October 2020, we enrolled 50 trans men into a cross‐sectional study through snowball sampling. Data were collected on socio‐demographic characteristics, sexual practices and depression. We conducted 20 qualitative interviews to explore: (1) descriptions of sexual practices that could increase HIV/STI exposure; (2) experiences of accessing public healthcare facilities; (3) perceptions of HIV or STI testing; (4) HIV and STI service delivery; and (5) drug and alcohol use. We used an inductive content analytic approach centring on descriptive category development to analyse the data. Results: The median age was 25 years (interquartile range 23–28). The prevalence of HIV, syphilis and hepatitis B was 4%, 6% and 8%, respectively. We observed multiple levels of intersecting individual, interpersonal and structural stigmas. (1) Trans men reported transphobic rape motivated by interpersonal stigma that was psychologically traumatizing to the survivor. The resultant stigma and shame hindered healthcare access. (2) Structural stigma and economic vulnerability led to sex work, which increased the risk of HIV and other STIs. Sex work stigma further compounded vulnerability. (3) Individualized stigma led to fear of disclosure of gender identity and HIV status. Concealment was used as a form of stigma management. (4) Multiple levels of stigma hampered access to healthcare services. Preference for trans‐friendly care was motivated by stigma avoidance in public facilities. Overall, the lived experiences of trans men highlight the intertwined relationship between stigma and sexual health. Conclusions: In this sample from Uganda, trans men experienced stigma at multiple levels, highlighting the need for gender‐sensitive healthcare delivery. Stigma reduction interventions, including provider training, non‐discrimination policies, support groups and stigma counselling, could strengthen uptake and utilization of prevention services by this marginalized population.